Teacher-student interactions as a pathway to strengthen working memory in primary school students: a microtrial study protocol - Sophie Pollé; Simona Sankalaite; Mariëtte Huizinga; Megan McClelland; Jantine L. Spilt; Dieter Baeyens (Frontiers in Education)
Executive function refers to a set of cognitive processes essential for effectively managing complex tasks and enabling goal-directed behavior. Working memory (WM), one of the core executive functions, is the ability to temporarily hold and manipulate information. It plays an important role in various cognitive tasks and learning processes, with WM difficulties greatly affecting students’ academic performance and overall learning. Despite clinical efforts to improve WM in primary school children, results have been inconsistent. Second-generation research has shifted focus to the role of environmental factors, such as teacher-student interactions (TSIs), as a means to better support students’ WM. Based on the Teaching through interactions framework, TSIs are categorized into three domains: instructional support, emotional support, and classroom organization. This study protocol aims to (1) elucidate the theoretical foundations of each type of support and its relationship to WM, (2) provide a comprehensive overview of the intervention procedure, with a specific focus on its development, and (3) lay the groundwork for four microtrials to explore the immediate effects of instructional support, emotional support, and classroom organization provided by the teacher, on student’s WM-related problematic behaviors and performance, compared to a teaching-as-usual (TAU) control group. Each intervention includes a coaching session followed by a 4-week implementation period, during which five high-potential strategies focused on one type of support are applied at the classroom level. To achieve this, 168 teachers, together with students (aged 6–12, exhibiting WM-related problematic behaviors) and parents will be recruited to participate in the study. After the pre-tests, the participants will be randomly assigned to one of three experimental groups or the TAU group. Post-tests will be conducted after intervention implementation. The findings are expected to enhance theoretical understanding of effective WM intervention components and contribute to the development of targeted strategies to strengthen WM in educational settings.